A high-throughput method for the quantitative analysis of auxins - Barkawi, L.S.; Tam, Y.-Y.; Tillman, J.A.; Normanly, J.; Cohen, J.D.
Auxin measurements in plants are critical to understanding both auxin signaling and metabolic homeostasis. The most abundant natural auxin is indole-3-acetic acid (IAA). This protocol is for the precise, high-throughput determination of free IAA in plant tissue by isotope dilution analysis using gas chromatography-mass spectrometry (GC-MS). The steps described are as follows: harvesting of plant material; amino and polymethylmethacrylate solid-phase purification followed by derivatization with diazomethane (either manual or robotic); GC-MS analysis; and data analysis. [13 C 6]IAA is the standard used. The amount of tissue required is relatively small (25 mg of fresh weight)and one can process more than 500 samples per week using an automated system. To extract eight samples, this procedure takes ~3 h, whether performed manually or robotically. For processing more than eight samples, robotic extraction becomes substantially more time efficient, saving at least 0.5 h per additional batch of eight samples.
Keywords: ACCURACY; ARTICLE; AUTOMATION; CONTROLLED STUDY; DATA ANALYSIS; DERIVATIZATION; HARVESTING; HIGH THROUGHPUT SCREENING; HORMONE DETERMINATION; ISOTOPE DILUTION ASSAY; MASS FRAGMENTOGRAPHY; NONHUMAN; PLANT TISSUE; PRIORITY JOURNAL; PROTEIN PROCESSING; PROTEIN PROCESSING; QUANTITATIVE ANALYSIS; ROBOTICS; SOLID PHASE EXTRACTION